An assessment of Russia's growth prospects in 2003 - 2010 - Ville Kaitila (The Research Institute of the Finnish Economy (ETLA), 2003)
We examine macroeconomic developments in Russia in the latter half of the 1990s and the beginning of the 21st century. In this context we discuss the exchange rate of the rouble, the world market price of oil and the significance of reforms. Then we analyse Russia's growth prospects by reviewing estimates in the literature and making an estimate of our own that shows what the ratio of gross fixed capital formation to gross domestic product should be to sustain a given long-run growth rate. A higher investment rate is necessary in order to maintain growth momentum in Russia. The continuation of reform policies would support growth prospects. – Russia ; economic growth ; investment ; reforms – – Tässä keskustelualoitteessa tarkastellaan Venäjän makrotaloudellista kehitystä 1990-luvun jälkipuoliskolla ja tämän vuosikymmenen alussa. Tätä taustaa vasten analysoidaan ruplan vaihtokurssin, öljyn maailmanmarkkinahinnan ja talouden uudistusten merkitystä. Tämän jälkeen tarkastelemme kirjallisuudessa esitettyjä arvioita Venäjän kasvumahdollisuuksista ja teemme oman laskelman, josta nähdään, mikä bruttopääomanmuodostuksen osuus bruttokansantuotteesta pitäisi olla, jotta tietty kasvuvauhti voidaan ylläpitää pitkällä aikavälillä. Investoinnit ovat tässä suhteessa avainasemassa ja niiden taustalla tärkeänä tekijänä on puolestaan uudistusten jatkaminen. – Venäjä ; kasvu ; investoinnit ; uudistukset
Keywords: 330; Wirtschaftsreform; Wirtschaftswachstum; Investition; Russland